1999
DOI: 10.1177/107906329901100305
|View full text |Cite
|
Sign up to set email alerts
|

Use of Physical Force as an Offense Characteristic in Subtyping Juvenile Sexual Offenders

Abstract: Juvenile sexual offenders were grouped based on whether they had ever used physical force or threats of force to commit an offense using self-reports on the Multiphasic Sex Inventory (MSI) and clinical records review. Subjects were 101 male offenders, 12 to 19 years, residing at a residential treatment facility. Cross-tabulation of self-report and records review were done to define three groups of offenders: rapists (i.e., those who used force), nonrapists, and deniers. These three groups were compared using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Oliver, Hall, and Neuhaus (1993), in a sample of 150 juvenile offenders, found that adolescent sex offenders scored significantly lower on Social Maladjustment (an index of antisocial attitudes) than violent and nonviolent youths and were also significantly less likely to be classified in I-4 compared with the other two groups. In a sample of 101 juvenile offenders, Butz and Spaccarelli (1999) found that the JI did not reliably differentiate among juveniles classified as rapists, nonsexual offenders, and deniers. However, in a juvenile sample of 30 hands-on sex offenders and 34 nonsexual offenders, Flores (2002) found that nonsexual offending youth scored significantly higher on the Social Maladjustment, Value Orientation, Alienation, and Asocial Index subscales.…”
Section: The Jesness Inventory: a Brief Theoretical Overview And Recementioning
confidence: 94%
“…Oliver, Hall, and Neuhaus (1993), in a sample of 150 juvenile offenders, found that adolescent sex offenders scored significantly lower on Social Maladjustment (an index of antisocial attitudes) than violent and nonviolent youths and were also significantly less likely to be classified in I-4 compared with the other two groups. In a sample of 101 juvenile offenders, Butz and Spaccarelli (1999) found that the JI did not reliably differentiate among juveniles classified as rapists, nonsexual offenders, and deniers. However, in a juvenile sample of 30 hands-on sex offenders and 34 nonsexual offenders, Flores (2002) found that nonsexual offending youth scored significantly higher on the Social Maladjustment, Value Orientation, Alienation, and Asocial Index subscales.…”
Section: The Jesness Inventory: a Brief Theoretical Overview And Recementioning
confidence: 94%
“…Johnson (1988) also found that coercion was extremely common such that 83 percent of abusive boys used it; however, 60 percent of the coercion was considered to be verbal threats or bribes. In a study by Butz and Spaccarelli (1999), adolescent sexual offenders were grouped according to whether they ever used physical force or threats o f force during the commission of a sexual assault. Those who did use force were considered to be rapists and were found to demonstrate significantly more sexual assault fantasies and predatory behaviours.…”
Section: Other Variables Associated With Sexual Offendingmentioning
confidence: 99%
“…Research has also demonstrated that people who report deviant sexual fantasies (e.g., rape) were more likely to use force or endorse rape supportive attitudes and were more likely to physiologically display sexual arousal to sexually coercive stimuli (plaud & Bigwood, 1997;Butz & Spaccarelli, 1999).…”
Section: Deviant Fantasies and Sexual Offendingmentioning
confidence: 99%
“…Research with juvenile sex offenders indicates that those who have used force to sexually offend are more likely to report assault related fantasies, predatory behaviors, greater levels of deviant sexual interest and a greater number of victims (Butz & Spaccarelli, 1999). Abel, Becker, Mittleman, Cunningham-Rathner, Rouleau and Murphy (1987) found that more than 40% of non-familial child molesters reported the development of deviant sexual fantasies prior to sexually offending.…”
Section: Deviant Fantasies and Sexual Offendingmentioning
confidence: 99%